Chiral porphyrin assemblies. Issue 1 (22nd April 2022) - Zhang, Li; Wang, Tianyu; Jiang, Jianzhuang; Liu, Minghua
Abstract: Porphyrins are among the most important macrocycles because they perform many essential functions in living systems and serve as building blocks in many functional materials. Incorporating the chirality into porphyrins can aid biomimetic research and the exploration of new functional materials. In this review, recent developments in chiral porphyrin assemblies are highlighted. The review is mainly divided into two sections: the different strategies for constructing chiral porphyrin assemblies and the applications. The formation of chiral porphyrin assemblies can be from porphyrin molecules substituted with chiral groups; achiral porphyrins induced by chiral additives and spontaneous deracemizations of achiral porphyrins during the assemblies. We also provide an overview of the applications of chiral porphyrin assemblies in chiral sensing, asymmetry catalysis, circularly polarized luminescence, and so on. The further challenge in the field is discussed. Abstract : The study of the chiral assembly of porphyrins can aid biomimetic research and the exploration of functional materials. In this review, recent developments of chiral porphyrins assemblies are highlighted. We also provide an overview of the applications of chiral porphyrin assemblies in the fields of sensing, catalysis, and optics.